2017
DOI: 10.1186/s13030-017-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain threshold reflects psychological traits in patients with chronic pain: a cross-sectional study

Abstract: BackgroundChronic pain enhances sensory sensitivity and induces the biased development of psychological traits such as depression and pain catastrophizing, leading to the formation of heterogeneous conditions. Fluctuations in the sensory-related thresholds of non-injured sites (with normal peripheral tissue) in patients with chronic pain are thought to be related to central sensitization. The objectives of this study were to analyze the association between pain tolerance thresholds (PTTs) in non-injured sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…In line with previous reports, our patients presented with abnormal levels of hypochondria, depression, hysteria and health concerns, as shown by the MMPI analyses [69]. The MMPI has been used to classify psychological traits of patients with chronic pain.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with previous reports, our patients presented with abnormal levels of hypochondria, depression, hysteria and health concerns, as shown by the MMPI analyses [69]. The MMPI has been used to classify psychological traits of patients with chronic pain.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, many studies demonstrated depressive symptoms and deficits in attention, verbal memory and executive functions within this syndrome [5]. It should also be said that altered personality profiles such as hysteria, hypochondria, depression or anxiety have been often reported following clinical measurements of personality traits in people with this condition [69]. All these notions lead to the conclusion that chronic pain, which refers to a multimodal experience, may contribute to disability, anxiety, depression, sleep disturbances, poor quality of life (QoL), and elevated healthcare costs [1012].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of pain thresholds in patients with chronic pain, there was a correlation between lower pain threshold and depressive tendency and hypochondriac concerns. 75 …”
Section: Discussionmentioning
confidence: 99%
“…17,28 The neurotic triad pattern is related to depressive tendencies, introversion, hypochondriacal anxiety, and catastrophizing often involved in pathological conditions associated with chronic pain; it has also been associated with low tolerance for and high sensitivity to pain. 43 However, few studies have investigated the specific personality traits of CRPS patients. A study of 17 patients with CRPS reported that their MMPI-2 profiles were similar to those of patients with conversion disorder.…”
Section: Discussionmentioning
confidence: 99%